Cubic B-Spline Collocation Method for One-Dimensional Heat and Advection-Diffusion Equations - Joan Goh; Ahmad Abd. Majid; Ahmad Izani Md. Ismail (Journal of Applied Mathematics)
Numerical solutions of one-dimensional heat and advection-diffusion equations are obtained by collocation method based on cubic B-spline. Usual finite difference scheme is used for time and space integrations. Cubic B-spline is applied as interpolation function. The stability analysis of the scheme is examined by the Von Neumann approach. The efficiency of the method is illustrated by some test problems. The numerical results are found to be in good agreement with the exact solution.